The impact of obesity and chronic PPAR Alpha agonist treatment on cardiac function, metabolism and ischaemic tolerance - Smith, Wayne (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.